A Study of Transgressed Boundaries in The Gate to Women’s Country by Sheri S. Tepper - Wiśniewska, Ewa (Text Matters: A Journal of Literature, Theory and Culture, 2024)
This paper endeavours to delineate the gender dynamics and ethical quandaries arising from the repercussions of war and the decisions undertaken to preserve societal norms, as depicted in the 1988 science-fiction novel entitled The Gate to Women’s Country, written by American author Sheri S. Tepper. Serving as a critique, the narrative provides insight into inquiries surrounding the supposed genetic determinants of violence. It interrogates established paradigms pertaining to gender, introducing a society meticulously crafted through scientific design.